2002
DOI: 10.1128/jvi.76.21.10756-10765.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Conferring Resistance to Neutralization by a Soluble Form of the Neurotrophin Receptor (p75NTR) Map outside of the Known Antigenic Sites of the Rabies Virus Glycoprotein

Abstract: The neurotrophin receptor (p75NTR) serves as a receptor for rabies virus (RV). We expressed and purified a soluble chimera consisting of the p75NTR ectodomain fused to the human immunoglobulin G1 (IgG1) Fc fragment (p75-Fc). Although p75-Fc interacts with RV, the infectivity of RV did not decrease significantly when it was incubated in the presence of the soluble receptor alone. However, when it was subsequently incubated with an antihuman IgG directed against the Fc fragment of p75-Fc, the infectivity of RV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 76 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…Using an expression cloning strategy, we have previously shown that p75 NTR can serve as a receptor for RVG (50). We have also show that a soluble form of p75 NTR can bind to RV and neutralizes its infectivity (31), indicating that p75 NTR is sufficient for RVG interaction and that no coreceptor is required. In the present study, we found that RV infection is restricted to a subpopulation of large-diameter, capsaicin-insensitive neurons and that the vast majority of infected neurons express p75 NTR .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Using an expression cloning strategy, we have previously shown that p75 NTR can serve as a receptor for RVG (50). We have also show that a soluble form of p75 NTR can bind to RV and neutralizes its infectivity (31), indicating that p75 NTR is sufficient for RVG interaction and that no coreceptor is required. In the present study, we found that RV infection is restricted to a subpopulation of large-diameter, capsaicin-insensitive neurons and that the vast majority of infected neurons express p75 NTR .…”
Section: Discussionmentioning
confidence: 90%
“…First, p75 NTR might require a cofactor that is not found in these neurons. This is unlikely, because we have shown that a soluble form of p75 NTR is able and sufficient to interact with RV and RVG on its own (31,46) and its affinity constant is 2 nM (46). Second, binding of RV is prevented, and there are several molecules which are tightly associated with p75 NTR and could modify its binding affinity (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations